Aldehyde dehydrogenase 2 polymorphism affects the outcome of methanol poisoning in exposed humans - Hubacek, J A; Jirsa, M; Bobak, M; Pelclova, D; Zakharov, S (Clinical genetics, 2018)
As the susceptibility of humans to xenobiotics often depends on genetic factors, we assumed that ADH1B and ALDH2 genetic variants may affect susceptibility to the acute methanol exposure. To evaluate the role of genetic variants of enzymes involved in methanol catabolism in humans, we analysed ADH1B (rs1229984) and ALDH2 (rs441) polymorphisms in 50 adults who survived acute methanol poisoning, 246 individuals with alcoholic liver cirrhosis, and in 545 healthy controls. GG homozygotes of ADH1B were more common among methanol-poisoned patients (98%) and among patients with alcoholic liver cirrhosis (98%) than among healthy controls (90%) (P = 0.08 and < 0.001, respectively). Minor C allele carriers of the ALDH2 were significantly more common among methanol-poisoned persons (46%) than among patients with alcoholic liver cirrhosis or healthy controls (31% in both groups, P < 0.05 and 0.025, respectively); the odds ratios were 1.89 (95% CI 1.02-3.52) and 1.94 (1.08-3.48), respectively. As there was a substantial amount of subjects with alcohol abuse between both groups of patients, ADH1B is unlikely to affect the susceptibility to methanol poisoning. By contrast, the genetic variant of the ALDH2 enzyme seems to specifically affect the susceptibility to methanol in acutely exposed humans and potentially plays a role in the outcome of methanol poisoning.
Keywords: alkoholismus; alely; Alleles; Aged; Genotype; Methanol; methanol; mitochondriální aldehyddehydrogenasa; lidé středního věku; senioři; genotyp; lidé; Adult; Middle Aged; dospělí; Alcoholism; jaterní cirhóza; jednonukleotidový polymorfismus; Liver Cirrhosis; Female; Polymorphism, Genetic; Polymorphism, Single Nucleotide; Aldehyde Dehydrogenase, Mitochondrial; odds ratio; polymorfismus genetický; Male; ženské pohlaví; mladý dospělý; Pharmacogenomic Variants; Humans; mužské pohlaví; Young Adult; farmakogenomické varianty; Odds Ratio